Highly Efficient Synthesis of 2-Substituted Benzo[b]furan Derivatives from the Cross-Coupling Reactions of 2-Halobenzo[b]furans with Organoalane Reagents - Wen, Chang; Wu, Chuan; Luo, Ruiqiang; Li, Qinghan; Chen, Feng (Synthesis, 2021)
A highly efficient and simple route for the synthesis of 2-substituted benzo[b]furans has been developed by palladium-catalyzed cross-coupling reaction of 2-halobenzo[b]furans with aryl, alkynyl, and alkylaluminum reagents. Various 2-aryl-, 2-alkynyl-, and 2-alkyl-substituted benzo[b]furan derivatives can be obtained in 23–97% isolated yields using 2–3 mol% PdCl2/4–6 mol% XantPhos as the catalyst under mild reaction conditions. The aryls bearing electron-donating or electron-withdrawing groups in 2-halobenzo[b]furans gave products in 40–97% isolated yields. In addition, aluminum reagents containing thienyl, furanyl, trimethylsilanyl, and benzyl groups worked efficiently with 2-halobenzo[b]furans as well, and three bioactive molecules with 2-substituted benzo[b]furan skeleton were synthesized. Furthermore, the broad substrates scope and the typical maintenance of vigorous efficiency on gram scale make this protocol a potentially practical method to synthesize 2-substituted benzo[b]furan derivatives. On the basis of the experimental results, a possible catalytic cycle has been proposed.
Keywords: 2-substituted benzo[b]furans; palladium; organoalane reagents; 2-halobenzo[b]furan; cross-coupling reaction